Thailand Public Finance Management Report : Government Spending and Central-Local Relations in Thailand’s Health Sector - Lindelow, Magnus (World Bank, Washington, DC, 2017)
This discussion paper is one of five discussion papers for the Thailand public financial management report. It focuses on efficiency and equity in the financing of health services, and the evolving role of central and local government in the health sector. Over the last few decades, Thailand has seen significant improvements in health outcomes, reflecting sustained public investment in both infrastructure and human resources. Thailand has also succeeded in expanding the coverage of health protection schemes, culminating in the introduction of the Universal Coverage (UC) scheme in 2001. These efforts have broadened access to health services, contributed to greater and more equitable utilization, and helped reduce the financial burden and the risk of impoverishment associated with health care expenses. However, there are fewer data on broader measures of health system performance, including dimensions of quality. Overall, available evidence suggests a mixed picture. For instance, while there has been improvement in the management of chronic conditions, a significant number of cases remain undiagnosed or untreated. Similarly, Thailand has seen recent improvement in 2-year survival rates from cancer and heart attacks, but still lags far behind Organization for Economic Co-operation and Development (OECD) countries. While the achievements of Thailand's health system are undeniable, this paper highlights three key challenges: (i) inequalities in utilization and spending; (ii) mounting cost pressures; and (iii) fragmentation of financing and unresolved issues concerning the respective roles of central and local government. This paper provides evidence of regional differences in diagnosis and management of chronic disease, and of survival rates from cancer and heart attacks. These data do not suggest a strong relationship between the health system and spending on the one hand, and on quality or health outcomes on the other. Indeed, efficiency may be a greater concern, with over-provision now a growing problem in some parts of the health system. However, more evidence is needed on these issues. For example, while high levels of spending and utilization in the Civil Servant Medical Benefit Scheme (CSMBS) are often noted, it is less clear whether this is associated with better outcomes (e.g. higher cancer survival rates or improved health outcomes for the elderly). The implications of geographic disparities in spending in the Social Security Scheme (SSS) and the CSMBS also warrant further attention.